Quercetin`s effect on cycling efficiency and substrate utilization - Dumke, C. L.; Nieman, D. C.; Utter, A. C.; Rigby, M. D.; Quindry, J. C.; Triplett, N. T.; McAnulty, S. R.; McAnulty, L. S. (Applied Physiology, Nutrition, and Metabolism, 2009)
Previous evidence suggests that quercetin supplementation increases performance in humans. We examined the effects of 3 weeks of quercetin supplementation on fuel utilization, gross efficiency (GE), and perceived effort during 3 h of cycling over 3 successive days. Forty cyclists were randomized into quercetin and placebo groups and tested for maximal oxygen consumption (53.2 ± 1.2 and 54.7 ± 1.1 mL/kg·min). For 3 weeks following maximal oxygen consumption testing, subjects supplemented either 1000 mg/day quercetin or placebo during normal training. Following supplementation, subjects cycled at 57% maximum power for 3 h, on 3 successive days, using their own bicycles fitted to CompuTrainer Pro Model trainers (RacerMate, Seattle, Wash.). Metabolic measurements were taken every 30 min for each 3-h ride. Muscle biopsies obtained from the vastus lateralis immediately pre-exercise and postexercise on days 1 and 3 were analyzed for muscle glycogen content. Power output remained constant for all 3 exercise trials, but significant decreases over time were measured for GE, cadence, respiratory exchange ratio, blood glucose, and muscle glycogen. Significant increases were measured for heart rate and volume of oxygen consumption over time. No quercetin treatment effect was observed for any of the outcome measures in this study. These data indicate that GE is reduced during an exhausting 3-h bout of exercise. However, quercetin did not significantly affect any outcomes in these already well-trained subjects.